Strategies for coping with psychological stress among students repeating the baccalaureate: a field study in Constantine high schools - Ouchenne, Amine; Soualmia, Farida (Journal of Human Sciences, 2022)
The aim of this study is to know the level of psychological stress and strategies for coping with psychological stress among students of repeaters for the baccalaureate. In order to verify the hypotheses of the study, we relied on the descriptive analytical approach, using the Levenstein scale and the CISS scale as study tools, which were applied to a non-randomized sample of 86 male and female students. The data was analyzed using frequencies, percentages and arithmetic averages, Mann-Wattney test, Croxall Wallis test. The study found that students repeating the baccalaureate use different coping strategies to face psychological stress, and there are no differences in strategies to confront stress at a level of significance of 0.05 is related to the variables (sex - division).